2010
DOI: 10.1093/chemse/bjq016
|View full text |Cite
|
Sign up to set email alerts
|

Adding Cocoa to Sucrose: The Effect on Cold Pain Tolerance

Abstract: The sweet taste of sucrose acts as an analgesic, whereas the taste of a bitter substance decreases pain tolerance. The present experiment explores the analgesic effect of a complex taste and asks how adding cocoa, a substance often associated with sweet foods but that has a bitter taste, to a sucrose solution affects cold pain tolerance. The 24 male participants were exposed to Cold Pressor Tests (CPTs) while holding 1 of 3 tastants in their mouths: water, sucrose, or sucrose with cocoa added. After each CPT, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 27 publications
2
21
0
Order By: Relevance
“…The results suggest that taste qualities, probably due to their values as a signal for nutrition, are responsible for mediating cold pain tolerance Eggleston et al (2010) Administration of flavanol-rich cocoa powder and spirulina…”
Section: Effects and Low-density Lipoprotein Oxidative Susceptibilitymentioning
confidence: 93%
“…The results suggest that taste qualities, probably due to their values as a signal for nutrition, are responsible for mediating cold pain tolerance Eggleston et al (2010) Administration of flavanol-rich cocoa powder and spirulina…”
Section: Effects and Low-density Lipoprotein Oxidative Susceptibilitymentioning
confidence: 93%
“…Through learning, chocolate's palatability and perceived pleasantness can become associated with increased levels of endogenous opioids [ 22 ] that may reduce pain perception. Furthermore, the increase in opioids may serve as a self-preservation function, since consuming a food of high nutritional value such as chocolate may be more evolutionarily important to an animal than a brief response to pain [ 18,37 ] .…”
Section: Discussionmentioning
confidence: 99%
“…It is worth mentioning, however, that chocolate's analgesic effects have not always been observed in humans. At least one study has observed that cocoa's addition to sucrose reduced pain tolerance in a cold-pressor test [ 18 ] . Still, given the number of historical and modern reports of the pain-relieving and medicinal properties of chocolate, it is worth examining the potential mechanisms that could contribute to chocolate analgesia.…”
Section: Modern Uses Of Chocolate In Pain Reliefmentioning
confidence: 99%
See 2 more Smart Citations